Project management for start-up businesses in F&B industry: A case study for milk tea shop in Vietnam - Duy, Nguyễn Đức; Tín , Tô Hữu; Ngân, Huỳnh Thị Thiên; Ngân, Phạm Nguyễn Thu; Huyền, Phạm Minh; Châu, Nguyễn Trần Vương (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2023)
Milk tea or Bubble tea is currently growing and becoming entirely developed. Through our investigation into how milk tea shops are constructed nowadays, we discovered that there are no precise plans for handling and building projects; instead, milk tea shops are merely created and controlled using manual solutions. Therefore, we utilize Work Breakdown Structure (WBS) to separate and organize work objects throughout the project scope to address this issue. WBS also aids in minimizing project risks and job-related variations with the person in charge of that activity. Moreover, we used Microsoft Project software to effectively plan, organize, and finish the construction of a milk tea establishment in compliance with the initial budget and schedule. By doing this, we can better understand how to design and manage a project and ensure its success.